Variation in Pediatric Anesthesiologist Sedation Practices for Pediatric Gastrointestinal Endoscopy - Hartjes, Kayla T.; Dafonte, Tracey M.; Lee, Austin F.; Lightdale, Jenifer R. (Frontiers in Pediatrics, 2021)
BACKGROUND: Despite a worldwide shift towards anesthesiologist-administered sedation for gastrointestinal endoscopy in children, ideal sedation regimens remain unclear and best practices undefined. AIM: The aim of our study was to document variation in anesthesiologist-administered sedation for pediatric endoscopy. Outcomes of interest included coefficients of variation, procedural efficiency, as well as adverse events. METHODS: IRB approval was obtained to review electronic health records of children undergoing routine endoscopy at our medical center during a recent calendar year. Descriptive and multivariate analyses were used to examine predictors of sedation practices. RESULTS: 258 healthy children (2-21 years (median 15, (Q1-Q3 = 10-17)) underwent either upper and/or lower endoscopies with sedation administered by anesthesiologists (n=21), using different sedation regimens (29) that ranged from a single drug administered to 6 sedatives in combination. Most patients did not undergo endotracheal tube intubation for the procedure (208, 81%), and received propofol (255, 89%) either alone or in combination with other sedatives. A total of 10 (3.8%) adverse events (9 sedation related) were documented to occur. The coefficient of variation (CV) for sedation times was high at 64.2%, with regression analysis suggesting 8% was unexplained by procedure time. Multivariable model suggested that longer procedure time (p<.0001), younger age (p<.0001), and use of endotracheal tube intubation (p=0.02) were associated with longer sedation time. DISCUSSION: We found great variation in anesthesiologist administered regimens for pediatric endoscopy at our institution that may be unwarranted, presenting may opportunities for minimizing patient risk, as well as for optimizing procedural efficiency.